2015
DOI: 10.1128/mcb.00294-15
|View full text |Cite
|
Sign up to set email alerts
|

Complete cis Exclusion upon Duplication of the Eμ Enhancer at the Immunoglobulin Heavy Chain Locus

Abstract: dDeveloping lymphocytes somatically diversify their antigen-receptor loci through V(D)J recombination. The process is associated with allelic exclusion, which results in monoallelic expression of an antigen receptor locus. Various cis-regulatory elements control V(D)J recombination in a developmentally regulated manner, but their role in allelic exclusion is still unclear. At the immunoglobulin heavy chain locus (IgH), the E enhancer plays a critical role in V(D)J recombination. We generated a mouse line with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Thus, recombination of distal but not proximal V H genes is inhibited in mice deficient in the histone-modifying enzyme EZH2 and in different transcription factors involved in V(D)J recombination, such as PAX5, YY1, and Ikaros (35)(36)(37)(38). Mutations targeting various cis-acting elements at the IgH locus similarly showed a differential effect on germ line transcription and recombination of proximal versus distal V H genes (12,16,(39)(40)(41)(42). Importantly, deletion of the 3=RR in the context of the 120-kb deletion had no effect on long-range interactions across the IgH locus in RAG2-deficient pro-B cells (22).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, recombination of distal but not proximal V H genes is inhibited in mice deficient in the histone-modifying enzyme EZH2 and in different transcription factors involved in V(D)J recombination, such as PAX5, YY1, and Ikaros (35)(36)(37)(38). Mutations targeting various cis-acting elements at the IgH locus similarly showed a differential effect on germ line transcription and recombination of proximal versus distal V H genes (12,16,(39)(40)(41)(42). Importantly, deletion of the 3=RR in the context of the 120-kb deletion had no effect on long-range interactions across the IgH locus in RAG2-deficient pro-B cells (22).…”
Section: Discussionmentioning
confidence: 97%
“…One prediction of this model is that deletion of the 3=RR will result in increased V H germ line transcription and V H -DJ H frequency, and we found this result in the present study. Another prediction is that if a heavy chain is expressed prematurely [that is, prior to V(D)J recombination], the 3=RR will be instructed to inhibit V H germ line transcription, and the outcome will be an impairment of V H -DJ H recombination; this is indeed the case (42). The wide impact of the 3=RR on sense and antisense germ line transcription within the variable region raises the question of whether the 3=RR targets sense and antisense promoters simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that replacement of Iγ3 switch promoter by a PV H -VDJ-Eµ cassette (hereafter A150 mutation or mouse line) ( Supplementary Figure 1A ) leads to an accumulation of partially rearranged DJ H alleles and a drastic reduction of V H -DJ H recombination ( 43 ). Consequently, IgM expression is severely impaired in A150 homozygous mice and B cell development is driven by IgG3 ( 43 ) (and Supplementary Figure 1B ). In this study, we used this mouse line to investigate if Sγ3 region, in its new setting, has acquired the recombinational properties of Sµ.…”
Section: Resultsmentioning
confidence: 99%
“…We reasoned that by putting a downstream S sequence under the control of the known elements that regulate Sµ, we could investigate if that S region can acquire Sµ properties. To this end, we used a mouse line in which Iγ3 promoter was replaced by a pre-rearranged VDJ-Eµ cassette ( 43 ), leaving intact the endogenous Sµ and Sγ3 regions. In this setting, the two S regions have roughly the same size, are almost equally distant from Eµ enhancer, but differ in the nature of their core repeats and the density of AID target motifs.…”
Section: Introductionmentioning
confidence: 99%